Given the quadratic equation: 3x^2 + 8x -13 = 0

We need to find the roots of the equation .

We will use the formula to find the answer.

We know that a= 3 b= 8 and c= -13

==> x= [ -b +- sqrt(b^2-4ac)]/2a

==> x1= [ -8 + sqrt(64-4*3*-13) ]/ 2*3

= [ -8 + sqrt(220)]/ 6

= ( -8 + 2sqrt55]/6

= (-4+sqrt55)/3

==> x2= ( -4-sqrt55)/3

Then the roots for the quadratic equation is:

**x= { (-4+sqrt55)/3 . (-4-sqrt55)/3 }**

We have to solve the equation 3x^2 + 8x - 13 = 0

3x^2 + 8x - 13 = 0

x1 = [-b + sqrt (b^2 - 4ac)]/2a

=> [ -8 + sqrt(64 + 156)]/6

=> -4/3 + sqrt (220)/6

=> -4/3 + (sqrt 55) / 3

x2 = -4/3 - (sqrt 55) / 3

**The solution of the equation is { -4/3 + (sqrt 55) / 3 , -4/3 - (sqrt 55) / 3 }**

3x^2 + 8x - 13 = 0

x1 = [-b + sqrt (b^2 - 4ac)]/2a

=> [ -8 + sqrt(64 + 156)]/6

=> -4/3 + sqrt (220)/6

=> -4/3 + (sqrt 55) / 3

x2 = -4/3 - (sqrt 55) / 3

The solution of the equation is { -4/3 + (sqrt 55) / 3 , -4/3 - (sqrt 55) / 3 }